A content analysis of actionable guidelines for Climate-Smart agriculture implementation in South Africa- communication for behavioral changes - Oladimeji Idowu Oladele; Simon C. Mjabuliseni Ngidi (Climate Services, 2025)
The actionable guidelines for climate-smart agriculture were developed as advisory and prescriptive activities to promote the adoption of climate-smart agriculture techniques. The coverage of the guidelines aligns with the agroecological principles which serve as the foundation for cleaner production. The content analysis explored the nexus between cleaner production- agroecological principles and climate-smart agriculture, by examining the scope and intensity of coverage of agroecological principles through the perspectives of extended parallel process, construal level theory, and information deficit model by the actionable guidelines. The results reinforce the non-mutual exclusivity and exhaustivity among the three concepts due to the overlapping of the practice and knowledge of the concepts; and that the communication of any of the concepts inadvertently covers the other in a way that coherence, complementarity, and coordination have been established. The communication in the actionable guidelines emphasizes the intention for desired results, current activities needed to be implemented, implementation steps rather than the danger posed by climate change, and future implications and theoretical issues as often with climate change reports and communication outlets. The practical implication of the findings is that communication on climate change should not be overtly scientific if it is to elicit behavioral change and that the efficacy of the communication outlets should be evaluated for effectiveness.